STUDI PEMANFAATAN KULIT KOPI ARABIKA (Coffee arabica L.) SEBAGAI MIKRO ORGANISME LOKAL (MOL) - A Ita Juwita; Arnida Mustafa; Risna Tamrin (Agroindustrial Technology, University of Trunojoyo Madura, 2017)
MOL (Mikro Organisme Lokal) is the result of local material decomposition withfermentation method. MOL contains macro and micro nutrients and microbial decomposers.The smaller coffee peel that will fermented, the faster MOL can be formed. To acceleratedecomposition in MOL solution, it can be added food source of bacteria such as coconut waterand brown sugar.The purpose of this study was to study the process of making MOL from coffee peel, toanalyze the content of nitrogen, phosphor, and potassium of MOL of coffee peel and todetermine the effect of fermentation time on nitrogen, phosphor, and potassium contents ofMOL that resulted.This study was conducted with 4 (four) treatments, week 1, 2, 3 and 4 and 1 factor andusing 2 times replicate. The parameter of testing used for making coffee peel as localmicroorganism are MOL volume, nitrogen, phosphor and potassium contents.The result of study showed that the highest mol volume obtained in week 4 of 8.5 ml andthe lowest in week 1 of 5 ml. They were obtained from 500 g coffee peel. Determination ofnitogen, phosphorus and potassium as a macro nutrients has been conducted. The result showedthat the highest nitrogen was found to be 0,0039% in week 1, 3 and 4 and the lowest in week 2with percentage 0.034 %. Determine of phosphorus showed that the highest phosphor wasobtained in week 2 wtih percentage 0.033 % and the lowest in week 4 of 0.018%, and the resultof potassium analyze, the highest obtained in week 2 of 0.035 % and the lowest in week 4 of0.014%